GENEROSITY IN INDONESIAN LITERATURE: AN IMPLICATION OF CHARACTER EDUCATION - Rokhyanto; Umi Salamah; Nurwakhid Mulyono; Endang Sumarti (Journey: Journal of English Language and Pedagogy, 2022)
The problem in this research is: what are the implications of philanthropic attitudes related to character education in Indonesian literature (novels)?. The aim is to find out the picture of generosity contained in Indonesian literary works related to character education. The benefits of the results of this research are as reading material or additional knowledge in studying and understanding literary works, especially events related to the generosity of figures in Indonesian literature. The method in this study uses a qualitative approach and the data of this research are in the form of words, phrases, sentences, dialogues of characters in Indonesian literary novels. The research data includes: items of philanthropy theory and character education as well as data sources, namely the text of Indonesian literary novels. The results of this study are expected to be used as an additional basic reference concept for researchers who are interested in further deepening literary research, especially the disciplines of philanthropy and character education. This writing produces kindness to the poor, kindness in prescribing medicine, not being arrogant, caring for abandoned babies, caring for others, helping sick people, helping children whose fathers are in prison.